Nanocompósito polimérico de blenda (PEAD/PEUAMM) com Óxido de Grafeno (OG) e Grafeno Comercial (XP) - Silva, Jullyani Mendes Duarte da (2022)
The preparation of nanocomposites is fundamental for the development of new materials with multifunctionality and high performance. This work aimed to prepare (nano)composites of blends (High Density Polyethylene (HDPE)/Ultra High Molecular Weight Polyethylene (UHMMPE) with graphene oxide (OG) and commercial graphene (XP), using the mixer Haake liner with subsequent compression molding. Initially, to obtain the graphene oxide, a chemical and physical treatment was carried out on the natural graphite flake, and then the polymeric blends were produced. Graphene XP was used as received in the preparation of the nanocomposites. The blends (HDPE/ UHMMPE) were prepared from the fusion of the mixture of 0, 10, 20 and 30% (p/p) of UHMMPE in HDPE, being chosen the blend with the best results of mechanical and thermal properties for the preparation of nanocomposites. The nanocomposites were produced from the blend with 10% (w/w) of UHMMPE in HDPE, with 1, 2 and 3 % (w/w) of OG, and with 1, 2 and 3 % (w/w) of XP, using the same methodology to obtain the polymeric blends. The OG and XP samples were both characterized by X-ray Diffractometry (XRD), Raman Spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR). Only the OG sample was characterized by Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The polymeric blends and nanocomposites had the thermal properties investigated by Differential Exploratory Calorimetry (DSC) and Thermogravimetry (TG) and the mechanical properties by tensile testing. Through the study of the thermal properties of the polymeric blends, it was verified that in the blend with 10% (w/w) of UHMMPE there was a co-crystallization while the other blends crystallized individually and successively in mixtures. The melting temperatures did not undergo significant changes, while the crystallization temperatures had a small increase as a function of the UHMMPE content. Regarding the mechanical properties of the blends, they obtained an increase in tensile strength when compared to pure HDPE. In the thermal properties, a gain in the thermal stability of the nanocomposites was observed with most amounts of added filler, OG and XP. Regarding the mechanical properties of the nanocomposites, it was found that there was a decrease in their mechanical strength when compared to the blend of 10% (w/w) of UHMMPE in HDPE, due to lack of homogeneity of fillers in the polymer matrix.